Motivasi Kerja Perangkat Desa Sambo Kecamatan Dolo Selatan Kabupaten Sigi - Zainuddin, Zainuddin (Jurnal ADMINISTRATOR, 2025)
The purpose of this study was to determine the Work Motivation of Village Apparatus, especially Sambo Village, Dolo Selatan District, Sigi Regency. This study used a qualitative method with a descriptive approach. The results of the study showed that the Work Motivation of Sambo Village Apparatus, Dolo Selatan District, Sigi Regency through analysis using Abraham Maslow's Theory in Robbin which includes (1) Physiological Needs, (2) Security Needs, (3) Social Needs, (4) Appreciation Needs, (5) Self-Actualization Needs, the author concluded that of the five indicators only one indicator was not met, namely the need for appreciation, this can be seen from the unfulfilled need for appreciation for Sambo Village Apparatus, Dolo Selatan District, Sigi Regency